Respuesta :
[tex]\mathbf f(x,y)=x^4y^5\,\mathbf i+x^5y^4\,\mathbf j[/tex]
We want a scalar function [tex]f(x,y)[/tex] whose gradient is equivalent to the vector field. That means
[tex]\dfrac{\partial f}{\partial x}=x^4y^5\implies f(x,y)=\dfrac{x^5y^5}5+g(y)[/tex]
[tex]\dfrac{\partial f}{\partial y}=x^5y^4\implies x^5y^4=x^5y^4+\dfrac{\mathrm dg}{\mathrm dy}[/tex]
[tex]\implies\dfrac{\mathrm dg}{\mathrm dy}=0\implies g(y)=C[/tex]
So (a)
[tex]f(x,y)=\dfrac{x^5y^5}5+C[/tex]
which means (b)
[tex]\displaystyle\int_{\mathcal C}\mathbf f\cdot\mathrm d\mathbf r=f(\mathbf r(1))-f(\mathbf r(0))=f(-1,3)-f(0,0)=-\dfrac{243}5-0=-\dfrac{243}5[/tex]
We want a scalar function [tex]f(x,y)[/tex] whose gradient is equivalent to the vector field. That means
[tex]\dfrac{\partial f}{\partial x}=x^4y^5\implies f(x,y)=\dfrac{x^5y^5}5+g(y)[/tex]
[tex]\dfrac{\partial f}{\partial y}=x^5y^4\implies x^5y^4=x^5y^4+\dfrac{\mathrm dg}{\mathrm dy}[/tex]
[tex]\implies\dfrac{\mathrm dg}{\mathrm dy}=0\implies g(y)=C[/tex]
So (a)
[tex]f(x,y)=\dfrac{x^5y^5}5+C[/tex]
which means (b)
[tex]\displaystyle\int_{\mathcal C}\mathbf f\cdot\mathrm d\mathbf r=f(\mathbf r(1))-f(\mathbf r(0))=f(-1,3)-f(0,0)=-\dfrac{243}5-0=-\dfrac{243}5[/tex]
(a)[tex]f(x,y)=\frac{x^5y^5}{5} +k[/tex]
(b) [tex]\int\limits_c {f} \, dr=\frac{-243}{5}[/tex]
We have [tex]F(x, y) = x^4y^5i + x^5y^4j, C: r(t) = t^3 - 2t, t^3 + 2t , 0 \leq t \leq 1[/tex]
(a). As F=∇f
[tex]F(x, y) = x^4y^5i + x^5y^4j\\[/tex]
So,
[tex]\frac{df}{dx} =x^4y^5\\f(x,y)=\frac{x^4y^5}{5} +g(y)\\\frac{df}{dy} =x^5y^4\\f(x,y)=\frac{x^5y^5}{5} +k\\\frac{dg}{dy} =0\\g(y)=k\\f(x,y)=\frac{x^5y^5}{5} +k[/tex]
Therefore, [tex]f(x,y)=\frac{x^5y^5}{5} +k[/tex]
(b) Now,
[tex]\int\limits_c {f} \, dr=f(r(1)-f(r(0))\\=-f(-1,3)-f(0,0)\\f(x,y)=\frac{x^5y^5}{5}+c \\f(-1,3)=\frac{(-1)^53^5}{5}+c\\f(0,0)=0+c\\\int\limits_c {f} \, dr=\frac{-243}{5} -0\\\int\limits_c {f} \, dr=\frac{-243}{5}[/tex]
Learn more:https://brainly.com/question/13993335